Functional asymmetry in the olfactory system of a flatfish, the Senegalese sole (Solea senegalensis) - Barata, Eduardo N. (2009)
The two olfactory epithelia of the family Soleidae are exposed to different water sources; the upper (right) epithelium samples the water column whereas the lower (left) samples interstitial water. Given that one of the major prey species of the Senegalese sole (Solea senegalensis) is the ragworm Hediste diversicolor which lives in the substrate, we hypothesized that the lower epitheliummay have evolved sensitivity to odorants released by the ragworm whereas the upper epithelium may be more involved in chemical communication and therefore is more sensitive to odorants released by conspecifics. Using a combination of solid-phase extraction, liquid chromatography linked to mass spectroscopy and electrophysiological recording from the olfactory epithelia (the electro-olfactogram), we identified a prey-related odorant (the aromatic amino acid, l-phenylalanine) and a conspecific-related odorant (the bile acid, taurocholic acid). The lower epitheliumwas significantly more sensitive to the former whereas the upper was more sensitive to the latter. Furthermore, cross-adaptation and pharmacological blockade of adenylate cyclase (SQ-22536) and phospholipase C signaling pathways (U73122) suggested that the receptors and transduction mechanisms involved, respectively, are different in the two epithelia; specific receptors for l-phenylalanine in the lower epithelium act via the phospholipse C pathway whereas specific receptors for taurocholic acid in the upper epithelium act via both adenylate cyclase and phospholipase C mediated pathways. These results are consistent with our hypothesis and suggest a functional asymmetry in the olfactory system of this flatfish. Funded by FCT (Portugal) grants no. SFRH/BD/16242/2004 and POCI/BIA-BMC/55467/2004.